2018
DOI: 10.23866/brnrev:2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Double or Triple Therapy in Chronic Obstructive Pulmonary Disease

Abstract: Although the Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy recommends triple therapy involving long-acting muscarinic antagonists (LAMAs), long-acting β 2-agonists (LABAs) and inhaled corticosteroids (ICS) only for further advanced patients, particularly for those at a high risk for exacerbation (GOLD D), triple therapy is widely prescribed in real-life management of chronic obstructive pulmonary disease (COPD), even in patients with mild or moderate COPD severity, likely because physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In any case, the step-up approach from dual bronchodilation to triple therapy proposed by the GOLD strategy [5] does not reflect the important differences in AECOPDs (they differ in aetiology, severity and biological substrate), and thus it is not tailored on the patient's specific needs to be treated [35,36]. Furthermore, we must ascertain the COPD phenotype so that addition of an ICS to the LABA/LAMA therapy offers real additional clinical value, regardless of a preventive effect on AECOPDs, and verify what kind of benefit it is, or whether dual bronchodilation must be preferred also because it should be a less expensive treatment in real life [36].…”
Section: What Do These Meta-analyses Suggest?mentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the step-up approach from dual bronchodilation to triple therapy proposed by the GOLD strategy [5] does not reflect the important differences in AECOPDs (they differ in aetiology, severity and biological substrate), and thus it is not tailored on the patient's specific needs to be treated [35,36]. Furthermore, we must ascertain the COPD phenotype so that addition of an ICS to the LABA/LAMA therapy offers real additional clinical value, regardless of a preventive effect on AECOPDs, and verify what kind of benefit it is, or whether dual bronchodilation must be preferred also because it should be a less expensive treatment in real life [36].…”
Section: What Do These Meta-analyses Suggest?mentioning
confidence: 99%
“…In any case, the step-up approach from dual bronchodilation to triple therapy proposed by the GOLD strategy [5] does not reflect the important differences in AECOPDs (they differ in aetiology, severity and biological substrate), and thus it is not tailored on the patient's specific needs to be treated [35,36]. Furthermore, we must ascertain the COPD phenotype so that addition of an ICS to the LABA/LAMA therapy offers real additional clinical value, regardless of a preventive effect on AECOPDs, and verify what kind of benefit it is, or whether dual bronchodilation must be preferred also because it should be a less expensive treatment in real life [36]. In effect, Fabbri and colleagues [37] have pointed out that the single-inhaler triple therapy versus inhaled corticosteroid plus long-acting b2-agonist therapy for chronic obstructive pulmonary disease (TRILOGY) [38] and single-inhaler extrafine triple therapy versus long-acting muscarinic antagonist therapy for chronic obstructive pulmonary disease (TRINITY) [39] studies have shown that triple therapy is effective in patients currently defined as GOLD severity B (i.e., highly symptomatic but at low risk of exacerbations, for whom longacting bronchodilators alone or in combination, but no combination that includes ICS, are still recommended [5]).…”
Section: What Do These Meta-analyses Suggest?mentioning
confidence: 99%
“…Combining Dual Bronchodilation and Inhaled Corticosteroids. The key question when treating a patient with COPD is no longer whether and/or when it is appropriate to switch the patient from a LABA/ICS regimen to a LABA/LAMA one, but rather what is the type of patient for which we can add an ICS to dual bronchodilation and, above all, when (Cazzola et al, 2018e)?…”
Section: F When Must An Inhaled Corticosteroid Be Added?mentioning
confidence: 99%
“…In any case, stepping-up from dual bronchodilation to triple therapy, an approach that has also been proposed by the 2019 GOLD recommendations 3 , deliberately ignores the fundamental differences in etiology, severity, and biological substrate of ECOPDs and consequently is not intended to treat the real needs of the patient 30 . It is important to determine whether and when the addition of an ICS to the LAMA/LABA combination really induces further clinical benefit, regardless of a preventive effect on ECOPDs, and establish the value of this benefit and also determine whether cost differences make the LAMA/LABA combination therapy preferable over triple therapy in real life.…”
Section: Adding An Inhaled Corticosteroidmentioning
confidence: 99%